RANCANGAN SISTEM INFORMASI BIAYA PEMBANGUNAN PERUMAHAN PADA PT. HALINA MUTIARA - Elzas - (JURNAL AKADEMIKA)
Systems running on PT. Halina Mutiara in the cost of housing construction is still using Ledger. But only as a temporary data recording, so the cost of housing construction not yet have a good database, while the computer facilities are available, resulting in data processing have not resulted in optimal report.With the data collection system of housing construction costs by using Visual Basic 6.0 programming lan guage, can facilitate the employees of PT. Halina Mutiara in housing construction cost of data collection and calculation processes of its material every day can be done in a computerized, so as to produce a complete report, fast and accurate, compared with the existing ways of working often takes considerable time and also common mistakes and misuse of the data contained in the field of development.